TRADITIONS AND INNOVATIONS IN THE METHODOLOGY OF TEACHING A FOREIGN LANGUAGE - Abdisalimova Kamola Sanjar qizi (Modern American Journals, 2026)
This article examines the interplay between traditions and innovations in the methodology of teaching foreign languages. It provides a comprehensive analysis of traditional teaching approaches that have shaped foreign language pedagogy over the years, as well as contemporary innovative methods that respond to the challenges of the modern educational environment. Particular attention is given to methods that foster communicative competence, critical thinking, and learner-centered education. The study highlights how integrating technological tools, interactive activities, and creative pedagogical strategies can enhance student engagement and motivation. Moreover, it underscores the necessity of balancing long-established teaching principles with new approaches to ensure effective language acquisition. The article serves as a resource for educators, curriculum developers, and researchers seeking to optimize foreign language instruction through a thoughtful combination of tradition and innovation.
Keywords: Foreign language teaching, methodology, traditional methods, innovative methods, pedagogical strategies, language acquisition, communicative competence, learner-centered education, educational technology, interactive learning.